A Sophisticated Author: Muhammad al-Bakri’s Life, Books and Persona - Hüseyin Yazıcı (Şarkiyat Mecmuası)
Two books published in Egypt in 1966 and 2013 are seen to have dealt with Muhammad Tawfīq al-Bakrī, the Egyptian cleric, author, critic and thinker whose lineage goes back to Abū Bakr through one lineage and to the Prophet Muhammad (pbuh) through another; however, no significant research apart from one article is found about him in Turkey. During my research, the 2013 book about him was seen to have been written in more detail and more scientifically than the 1966 book. Because al-Bakrī received the first degree of Nişan-ı Osmanî [Order of Osmanieh] and the Rank of Anatolia from Sultan Abdülhamid II, his visit was clearly an important one. Al-Bakrī was able to receive a good education thanks to his family’s financial means, and he received a diploma (i.e., teaching certificate) from Al-Azhar University at a very young age thanks to this education. This diploma rendered him competent in the religious field. Meanwhile, he was appointed sheikh of the al-Bakrī dervish order, sheikh in charge of the Sufi orders (masīkhat al-mashāyikh al-sūfiyya), and naqīb al-ashrāf [chief of the Prophet’s descendants], whose history is much older than that of the masīkhat al-mashāyikh al-sūfiyya. He was also appointed as a permanent member of the Advisory Board (Meclisu şûra'l-kavânîn) in 1892 and as a permanent member of the General Assembly (al-Jam‛iyyat al-Umumiyya) of the Egyptian Government. Along with these duties, al-Bakri’s close and warm relationship with Khedive Abbās II first and then Lord Cromer, a statesman appointed as the British representative to Egypt and the British consul-general, paved the way for him to become more prominent. When considering al-Bakri’s closeness to Sultan Abdülhamid II, his influence on Egyptian political life for a time, his little-known book al-Mustaqbal Li'l-Islām that was translated into Ottoman, and most importantly his persona as accepted in the literary field and especially in classical Arabic literature, he is undoubtedly a person who definitely needs to be made known publicly. Based on a scan and evaluation of the relevant sources, this article explains the life, books, and scientific persona of al-Bakrī, a man not very well known in Türkiye who lived for 62 years, almost 20 of which were spent in pain but filled with important works.